2015
DOI: 10.1007/s00406-015-0615-z
|View full text |Cite
|
Sign up to set email alerts
|

Faux pas recognition performance in a help-seeking population at clinical high risk of psychosis

Abstract: There is a growing body of evidence suggesting that patients with psychosis show impaired theory of mind (ToM). However, much remains to be understood as to whether ToM deficits occur in the premorbid or post-onset period of psychosis. Our primary aim was to examine empirically impairment on ToM tasks in a group of individuals with clinical high risk (CHR) of psychosis. Fifty CHR participants identified through the Structured Interview for Prodromal Syndromes and 52 age-/education-matched controls were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It is possible that patients have social cognition deficits as a trait marker, and in addition, these deficits may worsen with symptoms, indicating that it is both a trait and a state variable. Moreover, social cognitive deficits are already present even in patients at risk of psychosis (Thompson et al ., 2012; Ohmuro et al ., 2016; Zhang et al ., 2016) and deficits have even been found in unaffected first-degree relatives (Bora and Pantelis, 2013), this highlighting its trait properties.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is possible that patients have social cognition deficits as a trait marker, and in addition, these deficits may worsen with symptoms, indicating that it is both a trait and a state variable. Moreover, social cognitive deficits are already present even in patients at risk of psychosis (Thompson et al ., 2012; Ohmuro et al ., 2016; Zhang et al ., 2016) and deficits have even been found in unaffected first-degree relatives (Bora and Pantelis, 2013), this highlighting its trait properties.…”
Section: Discussionmentioning
confidence: 92%
“…Medicine 5 already present even in patients at risk of psychosis (Thompson et al, 2012;Ohmuro et al, 2016;Zhang et al, 2016) and deficits have even been found in unaffected first-degree relatives (Bora and Pantelis, 2013), this highlighting its trait properties. On the other hand, another relevant finding of our study is that cognitive reserve and neurocognition predicted social cognition, both at baseline and 2 years.…”
Section: Psychologicalmentioning
confidence: 96%
“…A few studies [e.g., in schizophrenia: Refs. (382384)] have highlighted the importance of insight and a potential relationship between this and social cognition. Self-ratings (or proxy ratings of, e.g., empathy) are rarely explored in terms of a relationship with scores on these social cognitive popular tasks, but the pattern of performance on a scale such as the IRI could aid interpretation of other social cognitive tasks, e.g., high PD scores could be associated with an aversive reaction to emotional stimuli, affecting attention focus and impairing performance (49).…”
Section: Discussionmentioning
confidence: 99%
“…In situations where the subject identified a FP, additional questions were asked to assess the subject’s understanding of the FP. Minor modifications were made for social contexts in Chinese culture, according to a preliminary survey using the FP prior to this study 31 . The Chinese version was very similar to the English version, with hits or clues remaining unchanged.…”
Section: Methodsmentioning
confidence: 99%